Floral Dissimilarity and the Influence of Climate in the Pliocene High Arctic: Biotic and Abiotic Influences on Five Sites on the Canadian Arctic Archipelago - Fletcher, Tamara; Feng, Ran; Telka, Alice M.; Matthews, John V.; Ballantyne, Ashley (Frontiers in Ecology and Evolution, 2017)
A recurring goal in ecological and paleoclimatic studies is to either forecast how ecosystems will respond to future climate or hindcast climate from past ecosystem assemblages. The Pliocene is a useful deep-time laboratory for understanding an equilibrium climate state under modern atmospheric CO2, and has been a focus for climate modelers. Accurate estimates of proxy data-model mismatch are hindered by the scarcity of well-constrained observations from well-dated sites in the High Arctic. Using a recently developed community-based approach (Climate Reconstruction Analysis using Coexistence Likelihood Estimation: CRACLE) compared with an established method (The Coexistence Approach: CA), and applied to extraordinary, permafrost-driven preservation of floras, we explore the climate and community assemblages at five Pliocene sites in the Canadian Arctic Archipelago The results suggest that climatic differences at this scale do not simply correlate to differences in community assemblage between sites. The threshold temperature for tree line is one important component, but other factors in the environment (e.g. soil characteristics) may drive dissimilarity of communities where the taxa could share the same climate space. Estimates from CRACLE agree with previous estimates where available, and generally fall within the ranges of CA. Mean annual temperatures were 22°C hotter (ranging from 0.8 to 6.2°C by species across sites) and mean annual precipitation 500 mm wetter (ranging from 530 to 860 mm by species across sites) during the Early to ‘mid’-Pliocene ( 3.6 Ma) when compared with modern climate station data in the Canadian Arctic Archipelago. Comparison of estimates for three levels of taxonomic input suggest judicious interpretation is needed when generic level identifications are used, especially in the Polar Regions. The results herein are a reminder of the large impact of non-climatic abiotic and biotic factors to be accounted for when predicting future ranges of communities under different climate conditions from the present, and when hindcasting climate from past ecosystem assemblages.